The Effect of Education and Unemployment Rate on Poverty Rate of 4 Cities in North Sulawesi - Gaby Dainty Julliet Roring; Donald Bismarck Rondonuwu (AIBPM Publisher, 2022)
Through this research, the factors that impact the poverty rate of 4 cities in North Sulawesi, which are education and unemployment rate, were analyzed out. Secondary data and panel data regression is used in this research. After the testing stage, the common effect model (CEM) was selected as the suitable model. This research also conducted a classical assumption, partial, and coefficient determination test. The results are that education negatively and significantly affects the poverty rate of 4 cities in North Sulawesi, and the unemployment rate positively and significantly affects the poverty rate of 4 cities in North Sulawesi. The provision of stimulant assistance and subsidies, more effective and targeted poverty alleviation programs, education funding assistance, skills development training programs, more jobs, support small and medium enterprises, reduction of outsourcing labor, and accepting the employee fairly without nepotism are expected to help in reducing poverty rate and solve poverty problems in 4 cities in North Sulawesi, and even more broadly.Keywords: Common Effect Model, Education, Panel Data Regression, Poverty Rate, Unemployment Rate.